Illumination optimization strategies to enhance hydrogen productivity and light conversion efficiency for photo-fermentation by Rhodobacter sphaeroides KKU-PS1 using a concentrated multi-substrate feedstock - Muhammad Alif Fitri, Hanipa; Tiang, Ming Foong; Abdullah Amru, Indera Luthfi; Mohd Shaiful, Sajab; Mimi Hani, Abu Bakar; Reungsang, Alissara; Lay, Chyi-How; Wu, Shu-Yii; Kamrul Fakir, Kamarudin; Peer Mohamed, Abdul (Elsevier Ltd, 2024)
With the use of biotechnology, hydrogen can be produced from wastewater rich in short-chain fatty acids. A previous study revealed the ability of Rhodobacter sphaeroides KKU-PS1 to produce biohydrogen from substrates mimicking succinate fermentation effluent. However, the process still requires optimization. Before illumination optimization, due to high concentration of the effluent, various effluent dilution factors ranging from 10 to 100 were compared, and the optimal dilution factor was determined to be 50. Light-emitting diode (LED) setups consisting of bands and tubes were compared, and various illuminated surface-to-volume ratios (S/V) were obtained. LED tubes were subsequently used for light intensity optimization in the range of 5–23 klux, revealing optimum light intensity at 15 klux, yielding 2202 mL H2/L and 13.8 mL H2/L/h as the cumulative hydrogen and maximum output rate, respectively. The lighting protocol at 15 klux and with a 6h–6h light-dark cycle improved the total light conversion efficiency by up to 3.1%. The study successfully optimized the process, with results rivalling those of a previous study using malate.